Krobia xinguensis, a new species of cichlid fish from the Xingu River drainage in Brazil (Teleostei: Cichlidae) - Kullander, Sven O. (Zootaxa, 2012)
Krobia xinguensis is described from localities in the headwaters and in the lower part of the rio Xingu. It is distinguishedfrom the other two species in the genus, K. guianensis and K. itanyi, primarily by deeper caudal peduncle, and details ofthe colour pattern, including contrasting interorbital stripes and a small dark spot anteriorly on each side of the lower jaw.Krobia xinguensis represents a considerable range extension of the genus from the Guianas and northern tributaries of the lower Amazon, into a major south bank Amazon tributary.